CHARACTERISTIC OF CLINIC AND DIAGNOSTICS OF ERYSIPELAS. REVIEW - N. F. Plavunov; V. A. Kadyshev; T. Ya. Chernobrovkina; L. N. Proskurina (Архивъ внутренней медицины)
Erysipelas is one of the first places on the prevalence of infectious disease after acute respiratory and intestinal infections, viral hepatitis. Currently, in most cases erysipelas is caused by beta-hemolytic group A Streptococcus bacterium, but in some cases could be due to co-infection with Staphylococcus aureus. The pathogenesis of erysipelas is characterized by impaired tissue immunity, cellular and humoral immunity deficiency, hypersensivity to hemolytic streptococci group A (Lansfeld). Chronic recurrent erysipelas refers to endogenous infection caused by intradermal and intra-macrophage maintaining L-forms of Streptococcus, and biological damage caused by excess production of cytokines by T-lymphocytes and mononuclear cells. The disease is characterized by increased cases with primary and severe hemorrhagic forms (over 60%), a tendency to develop recurrent erysipelas (30 to 40%), slow regenerative process in the focus of inflammation, the multiplicity of the differential diagnosis. Risk factors of the erysipelas are the disruption of the skin barrier, fungal skin infections, emotional stress, body hypothermia or overheating. Women suffer from erysipelas more often than men. Adults over age 40 years and older are more likely to develop erysipelas in more than 60% of cases. Erysipelas is characterized by seasonality- rise in the incidence observed in spring and autumn than other streptococcal infections. Depending on the lack of treatment efficacy in resolving symptoms of erysipelas, impaired prevention of disease recurrence, recommended treatment by scientists involves antibiotics with immunomodulation therapy and laser therapy.